Role of Startups on Indian Economy - Dr. Meenakshi Bindal; Dr. Bhuwan Gupta; Sweety Dubey (International Journal of Engineering and Management Research, 2018)
India needs 10 million jobs a year and global data shows that it is startups, not large enterprises that create net new jobs in any country. Startups are the centers of innovation and are a great way to enhance employment creation in the economy. The concept of Start –up India campaign was started on 15th August 2015. Startups involve dealing with new technology which generally lies at the highest end of value addition chain. India is a home to almost 3100 startups starting per year standing just behind the US, UK, and Israel according to the NASSCOM report of 2015. If the growth continues in the same pace then it is expected that Indian tech startups will generate almost 2.5 lakh jobs in the next five years. India is also said to enjoy demographic dividend and it is anticipated that by 2020 India will be a home to 112 million working population falling in the age bracket of 20-24 years as compared to that of 94 million workers of China. This demographic dividend will definitely boost the startup culture in the country. The Prime Minister’s Startup India campaign is a great initiative to boost entrepreneurship in India. This initiative will play a very important role in further facilitating startups and providing a new dimension to entrepreneurship in the country.